Disturbance, colonization and development of Antarctic benthic communities - Barnes, David K.A (The Royal Society, 2006)
A decade has yielded much progress in understanding polar disturbance and community recovery—mainly through quantifying ice scour rates, other disturbance levels, larval abundance and diversity, colonization rates and response of benthos to predicted climate change. The continental shelf around Antarctica is clearly subject to massive disturbance, but remarkably across so many scales. In summer, millions of icebergs from sizes smaller than cars to larger than countries ground out and gouge the sea floor and crush the benthic communities there, while the highest wind speeds create the highest waves to pound the coast. In winter, the calm associated with the sea surface freezing creates the clearest marine water in the world. But in winter, an ice foot encases coastal life and anchor ice rips benthos from the sea floor. Over tens and hundreds of thousands of years, glaciations have done the same on continental scales—ice sheets have bulldozed the seabed and the zoobenthos to edge of shelves. We detail and rank modern disturbance levels (from most to least): ice; asteroid impacts; sediment instability; wind/wave action; pollution; UV irradiation; volcanism; trawling; non-indigenous species; freshwater inundation; and temperature stress. Benthic organisms have had to recolonize local scourings and continental shelves repeatedly, yet a decade of studies have demonstrated that they have (compared with lower latitudes) slow tempos of reproduction, colonization and growth. Despite massive disturbance levels and slow recolonization potential, the Antarctic shelf has a much richer fauna than would be expected for its area. Now, West Antarctica is among the fastest warming regions and its organisms face new rapid changes. In the next century, temperature stress and non-indigenous species will drastically rise to become dominant disturbances to the Antarctic life. Here, we describe the potential for benthic organisms to respond to disturbance, focusing particularly on what we know now that we did not a decade ago.